2013
DOI: 10.3109/0886022x.2013.819767
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure and pregnancy: a seventeen-year experience of a Tunisian intensive care unit

Abstract: To describe the epidemiologic features of acute renal failure related to pregnancy (PRARF) and to evaluate its prognostic impact. Methods: Retrospective study conducted in a Tunisian intensive care unit over a period of 17 years (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011). Women were included if they were more than 20 weeks pregnant and were admitted to the ICU during pregnancy or immediately (57 d) post partum. PRARF was defined by a serum creatinine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The diagnosis and treatment of AKI occurring during pregnancy, known as pregnancy-related AKI (PR-AKI), is a clinical challenge for obstetricians and nephrologists. The incidence and etiology of PR-AKI varies greatly between different regions (2)(3)(4)(5), and it has been reported that the incidence of PR-AKI in developed countries There is a high degree of heterogeneity in the definition of PR-AKI (2). Based on the existing literature, previously healthy pregnant women are considered to have developed AKI if they display an absolute increase in the serum creatinine (Scr) level of !…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis and treatment of AKI occurring during pregnancy, known as pregnancy-related AKI (PR-AKI), is a clinical challenge for obstetricians and nephrologists. The incidence and etiology of PR-AKI varies greatly between different regions (2)(3)(4)(5), and it has been reported that the incidence of PR-AKI in developed countries There is a high degree of heterogeneity in the definition of PR-AKI (2). Based on the existing literature, previously healthy pregnant women are considered to have developed AKI if they display an absolute increase in the serum creatinine (Scr) level of !…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, mortality among AKI patients was 20.6%, significantly higher than in those without this complication. Bouaziz et al 26 have also found a higher mortality among critically ill patients with AKI in comparison with those without AKI (9.3% vs. 1.7%, p < 0.001).…”
Section: Discussionmentioning
confidence: 91%
“…23 These laboratory abnormalities are probably associated with liver disorders, coagulation disturbances and HELLP syndrome. 2,8,[24][25][26][27] Regarding treatment, the use of vasoactive drugs, antibiotics, diuretics and mechanical ventilation were more frequent among AKI patients, which reflect the clinical severity of these patients. Mechanical ventilation and use of vasoactive drugs are associated with maternal mortality according to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective observational study in India, Gopalakrishnan et al reported preeclampsia as one of the causes of renal impairment in pregnancy [22]. In another retrospective study in Tunisia, Bouaziz et al [23] reported preeclampsia as the leading cause of renal impairment in pregnancy. While Peng [24] in a retrospective study conducted in Beijing, suggested both GH and PE as the primary cause of renal disease.…”
Section: Discussionmentioning
confidence: 99%